Anticancer Activity of Half‐Sandwich RhIII and IrIII Metalla‐Prisms Containing Lipophilic Side Chains. Issue 4 (11th March 2014) - Gupta, Gajendra; Mahesh Kumar, Jerald; Garci, Amine; Rangaraj, Nandini; Nagesh, Narayana; Therrien, Bruno
Abstract Two hexacationic pentamethylcyclopentadienyl rhodium(III) and iridium(III) metalla‐prisms, [(η5‐C5Me5)6M6(μ3‐tpt‐κN)2(μ4‐C6HRO4‐κO)3]6+ (tpt=2, 4, 6‐tri‐(pyridin‐4‐yl)‐1, 3, 5‐triazine; R=(CH2)10CH3; M=Rh, [3]6+; M=Ir, [4]6+) isolated as their triflate salts, have been synthesised from the dinuclear complexes (η5‐C5Me5)2M2(μ4‐C6HRO4‐κO)Cl2 (M=Rh, 1; M=Ir, 2) and AgCF3SO3. The antiproliferative activity of the neutral and cationic complexes has been evaluated in vitro in human cancer cell lines. The positively charged metalla‐prisms appear to target mitochondria, which ultimately induce apoptosis in cancer cells. All biological studies suggest that the rhodium derivative [3][CF3SO3]6 possesses excellent activities, not only in vitro but also in vivo in tumour‐induced C57L6/J mice.